The Customary of the Shrine of St. Thomas Becket at Canterbury Cathedral : Latin Text and Translation. - Jenkins, John. (Amsterdam : Arc Humanities Press, 2022)
This facing-page Latin and English edition of the customary for the shrine of St. Thomas Becket at Canterbury Cathedral, provides valuable insights into the management of one of the most popular pilgrimage sites in Europe.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books